Teaching Marketing Research at the University Level—From Academic and Professional Perspectives - de la Ballina, Javier; Cachero, Silvia (Sustainability, 2023)
The evolution of marketing research (MR) has run parallel to marketing; however, nowadays, statistical techniques and data technologies are gaining more importance. The need for alignment regarding MR training between professors, students, and professionals is becoming increasingly urgent. This work continues on a double survey administered to professors and MR professionals in Spain to determine their proposals for adapting MR courses’ format and content to the companies’ current information needs. The results show that not only do professionals lead in terms of wanting changes to training, but also that these professionals are by no means extreme in their demands regarding university professors. The findings also show that, although there are significant differences in priorities at both the statistical and technical levels, the solution may be to combine and slightly adjust the current mandatory MR courses in business administration degrees. In addition, an elective course that develops training in new data and intelligent technologies for MR should be implemented.